Error Analysis: Types and Causes of EFL Learners’ Errors in Writing Analytical Exposition Text - Mertosono, Sudarkam R.; Erniwati, Erniwati (Makassar State University, 2023)
Abstract. This research looked at errors made by the sophomores majoring in English Education of Tadulako University in writing analytical exposition text. It intends to (1) identify the kinds of errors committed by the students in writing the text, and (2) determine the causes of the errors. This is a-qualitative research, employing 20 students enrolled in Text Type Writing course in the Academic Year 2020. Results of the data analysis indicated that there were 421 cases of errors which were then classified into five major categories: orthographic errors, word forms and grammar (morpho-syntactic errors), errors on words and meanings (lexico-semantic), errors in punctuation and errors in capitalization. These errors are caused by influence of the students’ first language (L1) (interlingual errors), lack of target language knowledge (intralingual errors), and communication strategies. This paper addresses error analysis using Dulay’s 1982 Linguistic Category Taxonomy, which so far lack considerably in scientific literature. Previous studies have almost exclusively focused on using Surface Structure Taxonomy, another taxonomy is therefore needed for investigation. Keywords: Analytical Exposition Text, Error Analysis, Writing Skills